Improvement Innovation Environmental Management by PT Pertamina Patra Niaga Fuel Terminal Sei Siak - Riyadiyanto Riyadiyanto; Siti Maisarah (Ridwan Institute, 2022)
This study describes the implementation of several innovations at PT Pertamina Patra Niaga Fuel Terminal Sei Siak Pekanbaru. The implementation of this implementation program is focused on improving environmental management. The innovation program is a social innovation system that integrates the process of energy efficiency, emission reduction, reduction of B3 and non-B3 solid waste, water efficiency, and pollutant load by prioritizing and paying attention to the analysis of the impacts that will be caused. This study was conducted using descriptive qualitative methods and data collection techniques carried out by in-depth interviews with PT Pertamina Patra Niaga Fuel Terminal Sei Siak, as well as a literature study on the implementation of innovation. The innovation program carried out by PT Pertamina Fuel Terminal Sei Siak has resulted in a configuration of social innovations that can provide significant benefits in efforts to improve environmental management.